Endothelin B receptor gene hypermethylation in prostate adenocarcinoma. Issue 1 (1st January 2003) - Jerónimo, C; Henrique, R; Campos, P F; Oliveira, J; Caballero, O L; Lopes, C; Sidransky, D
Abstract : Background: Alterations in the methylation patterns of promoter CpG islands have been associated with the transcriptional inhibition of genes in many human cancers. These epigenetic alterations could be used as molecular markers for the early detection of cancer—that is, while potentially curable according to current therapeutic strategies. In prostate cancer, GSTP1 hypermethylation is the most common epigenetic alteration, and can be detected in up to 90% of cases. Thus, screening for methylation of other loci would probably increase the number of primary tumours amenable to screening. Moreover, previous studies have shown that the endothelin B receptor (EDNRB) gene is abnormally methylated in a high proportion of prostate tumours (∼70%). Aims: To investigate the potential use of EDNRB gene hypermethylation as a prostate cancer specific marker. Methods: Methylation specific polymerase chain reaction (MSP) for the promoter region of EDNRB was performed on prospectively collected tissue samples from 48 patients harbouring clinically localised prostate cancer, and in a group of 23 patients with benign prostatic hyperplasia (BPH). Genomic DNA was isolated from the samples and the methylation status was examined in a blinded manner. Results: EDNRB methylation was found in 40 of 48 of the adenocarcinomas. However, the same alteration was found in the paired normal tissue, and 21 of 23 of the BPH samples were found to harbour EDNRB hypermethylation. Conclusions: EDNRB hypermethylation at CpG sites upstream of the transcription start site can be detected in a high proportion of prostate adenocarcinomas. However, because this same alteration is also present in normal and hyperplastic tissue, it does not distinguish normal from neoplastic prostate cells, thus precluding its use as a prostate cancer marker.